Day 4 Fri, March 25, 2016 2016
DOI: 10.4043/26460-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drilling Fluid on Rock Mechanical Properties at Near-Drilling Conditions: An Implication of Fluid Design on Wellbore Stability

Abstract: Selecting a drilling fluid from the learnings from conventional reservoirs can be a wrong choice when it is used for unconventional formations. Drilling fluid has a chemo-mechanical effect on the reservoir rock during exposure time; this interaction can be abrupt or imperceptible depending on minerals comprising the rock matrix and their chemical sensitivity to the fluid composition. Improper selection of drilling fluid may cause strong shale-fluid interaction and thus result in wellbore instability. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
8
0
3
Order By: Relevance
“…W niektórych przypadkach lateks dodawany do płuczki wiertniczej łącznie z kompleksem glinowym może wpływać na zmniejszenie przenikania ciśnienia porowego skał łupkowych. Ograniczenie wzrostu ciśnienia, pod jakim płuczka wiertnicza wnika w matrycę skały łupkowej, jest jednym z ważniejszych czynników decydujących o zachowaniu stabilności ścian otworu wiertniczego (Wu et al, 2006;Vickers et al, 2007;Onuoha et al, 2011;Witthayapanyanon et al, 2013;Chao et al, 2014;Rea et al, 2016;Yadav et al, 2016).…”
Section: Część Teoretycznaunclassified
“…W niektórych przypadkach lateks dodawany do płuczki wiertniczej łącznie z kompleksem glinowym może wpływać na zmniejszenie przenikania ciśnienia porowego skał łupkowych. Ograniczenie wzrostu ciśnienia, pod jakim płuczka wiertnicza wnika w matrycę skały łupkowej, jest jednym z ważniejszych czynników decydujących o zachowaniu stabilności ścian otworu wiertniczego (Wu et al, 2006;Vickers et al, 2007;Onuoha et al, 2011;Witthayapanyanon et al, 2013;Chao et al, 2014;Rea et al, 2016;Yadav et al, 2016).…”
Section: Część Teoretycznaunclassified
“…Xu et al [15] showed that there is a strong relationship between rock UCS and E, where the relation degree changed from rock type to another as sandstone and mudstone and that is because of the rock lithology. Yadav et al [29] performed an experimental work to address the change in geomechanical properties (Young's modulus, Poisson's ratio, and peak strength) of Berea sandstone and shale samples after interaction with water-based mud (WBM) and oil-based mud (OBM). Using the triaxial test, they found that OBM is better than WBM in preserving the shale strength.…”
Section: Of 18mentioning
confidence: 99%
“…nowy rodzaj płuczki wiertniczej HPWBM (High Performance Water-Based Mud). Wraz z wdrożeniem do wierceń nowej generacji płuczek wiertniczych HPWBM zawierających w swoim składzie nowe rodzaje związków chemicznych (aminy, poliaminy, polieteroaminy) mających na celu zmniejszenie lub znaczące opóźnienie ich interakcji ze skałami ilasto-łupkowymi problemy niestabilności otworu zostały znacznie ograniczone (Ewy i Morton, 2009;Zhang et al, 2015;Yadav et al, 2016;Uliasz et al, 2018). Jednak niedogodności związane z oblepianiem świdra, aglomeracją i akrecją zwiercin w otworze nadal występują.…”
Section: Wprowadzenieunclassified